Pola Asuh Orang Tua Dalam Pembentukan Karakter Anak di Dusun Malaka Desa Mekarsari Kecamatan Gunungsari Kabupaten Lombok Barat - Ni Putu Desy Trisnayanti; Putu Wisnu Saputra (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2022)
ABSTRACT (Style Abstrak_3_BA) Parenting style is very important role in shaping the character of children. Parents have duties and obligations in instilling positive character from an early age, so that children can become individual beings who are ethical, have noble character and can socialize and adapt to their environment so that when they grow up they are expected to have positive characters. social. Like a social phenomenon that often occurs among children, whether it's a problem of bullying or the attitude of a child who is shy so they don't get along and are envious of one another. For this reason, parenting in shaping the character of children from an early age at home is very important for children's attitudes in the social environment. From this background, the following problems can be formulated: 1. How is parenting style in shaping the character of children in Malaka Hamlet, Mekarsari Village, Gunungsari District, West Lombok Regency? 2. What is the attitude of the children in Malacca Hamlet? The purpose of this study is 1.To determine the parenting style of parents in shaping the character of children in the Malaka Hamlet, Mekarsari Village, Gunungsari District, West Lombok Regency. To direct and solve the problems studied, two theories are used, namely classical conditioning theory and behavioristic theory. Judging from the type and nature, this research is a type of qualitative research. The methods used for data collection are non-systematic observation methods, free guided interviews and documentation. To analyze it with data reduction, data display and data verification. To check the validity of the data with credibility, dependability, conformability and transfermability. The results showed that parents in Malaka Hamlet used democratic and permissive parenting styles, from the parenting used it can be seen that of the eighteen indicators of character education there are nine indicators of character formed, this can be seen from the attitude of the children, namely religious, honest, tolerance, hard work, independence, respect for achievement, communicative, care for the environment and responsibility. Keywords: Parenting, parents, character building, children.